Bringing Asha Home - Krishnaswami, Uma 1956-; Akib, Jamel (New York : Lee & Low Books, 2006)
Eight-year-old Arun waits impatiently while international adoption paperwork is completed so that he can meet his new baby sister from India.
Keywords: East Indian Americans -- Fiction; Adoption -- Fiction; Siblings -- Fiction; Infants -- Fiction